Knowledge transfer in offshore insourcing : A case study of Nordic MNC in knowledge-intensive business services - Lagerspetz, Simo (My University, 2020)
Offshoring is a major part of globalized economy as advances in communications technology and logistics have allowed production to be located in practically anywhere regardless of the market the production serves. Especially offshoring of knowledge-intensive business services has benefitted from the advances in communications technology, as companies are able to choose the location of the production freely according to their needs. Knowledge transfer is a vital part of offshoring, especially in offshoring of services, and success of knowledge transfer has a large impact on the success of the offshore. The case in this study is an offshoring transition of a knowledge-intensive business service unit of a Nordic MNC from Finland to Eastern Europe. This research was conducted as an ethnographic research with participant observation method and the researcher had a significant role in the offshore transition. The previous literature about knowledge transfer and knowledge transfer in offshoring and service contexts were reviewed to form a perspective about what impacts the effectiveness of knowledge transfer and which challenges knowledge transfer has. Due to the focus of the previous literature, and the position the researcher had in the organization, the study focuses on the challenges that the employees conducting the knowledge transfer experience. Data was gathered by observing the knowledge transfer and the actions of the employees as well as by interviewing the employees who participated into the transition. The transfer of technical and explicit knowledge happened rather smoothly, but the transfer of tacit knowledge encountered issues. Previous experience of the employees was found to be a significant hinderance to transfer of tacit knowledge, as the recipients had difficulties to adopt new habits and methods. Similarly, the communication between the sources and the recipients, and the organization and the recipients were problematic and resulted in issues that had a negative effect on the knowledge transfer. These issues were caused by the differences in cultures of the recipients and sources, as well as due to the differences in the needs and the goals of the recipients and the organization.

Tuotannon siirto ulkomaille on tärkeä osa globalisoitunutta taloutta, koska viestintäteknologian ja logistiikan kehitys on mahdollistanut tuotannon sijoittamisen käytännössä mihin tahansa, riippumatta siitä mitä markkinoita tuotanto palvelee. Erityisesti tietointensiivisten yrityspalvelujen siirtäminen on hyötynyt viestintäteknologian kehityksestä, sillä yritykset pystyvät valitsemaan tuotannon sijainnin vapaasti omien tarpeidensa mukaan. Tiedonsiirto on elintärkeä osa tuotannon siirtämistä ulkomaille, etenkin palveluiden siirtämisen kohdalla, sillä tiedonsiirron onnistumisella on suuri vaikutus siirron onnistumiseen. Tämän tutkimuksen tapauksena on pohjoismaisen monikansallisen yrityksen tietointensiivisen yrityspalveluyksikön siirtäminen Suomesta Itä-Eurooppaan. Tämä tutkimus suoritettiin etnografisena tutkimuksena osallistuvalla havainnointimenetelmällä, missä tutkijalla oli merkittävä rooli yksikön siirtämisessä. Aikaisempaa kirjallisuutta tiedonsiirrosta, tiedonsiirrosta ulkomaille, sekä tiedonsiirrosta palvelukontekstissa, tarkasteltiin näkemyksen muodostamiseksi siitä, mikä vaikuttaa tiedonsiirron tehokkuuteen ja mitä haasteita tiedonsiirrossa esiintyy. Edellisen kirjallisuuden painopisteen ja tutkijan aseman vuoksi tutkimuksessa keskitytään haasteisiin, joita tiedon siirtäjät kokevat. Tietoja kerättiin tarkkailemalla tiedon siirtoa ja työntekijöiden toimia, sekä haastattelemalla muutokseen osallistuneita työntekijöitä. Teknisen ja eksplisiittisen tiedon siirto tapahtui melko sujuvasti, mutta hiljaisen tiedon siirtämisessä ilmeni ongelmia. Työntekijöiden aiemman kokemuksen havaittiin olevan merkittävä este hiljaisen tiedon siirtämiselle, sillä kokeneilla vastaanottajilla oli vaikeuksia omaksua uusia tapoja ja menetelmiä. Samoin lähteiden ja vastaanottajien, sekä organisaation ja vastaanottajien välinen viestintä oli ongelmallista ja johti ongelmiin, millä oli kielteinen vaikutus tiedon siirtoon. Ongelmat johtuivat vastaanottajien ja tiedon lähteiden keskinäisistä kulttuurieroista, kuin myöskin vastaanottajien ja organisaation tarpeiden ja tavoitteiden eroista.
Keywords: Knowledge Transfer, Offshoring, KIBS